Analysis of Different Methodologies to Calculate Bouguer Gravity Anomalies in the Argentine Continental Margin - Pedraza De Marchi, Ana Carolina (2014)
We have tested and used two methods to determine the Bouguer gravity anomaly in the area of the Argentine continental margin. The first method employs the relationship between the topography and gravity anomaly in the Fourier transform domain using Parker’s expression for different orders of expansion. The second method computes the complete Bouguer correction (Bullard A, B and C) with the Fortran code FA2BOUG2. The Bouguer slab correction (Bullard A), the curvature correction (Bullard B) and the terrain correction (Bullard C) are computed in several zones according to thedistances between the topography and the calculation point. In each zone, different approximations of the gravitationalattraction of rectangular or conic prisms are used according to the surrounding topography. Our calculations show that the anomaly generated by the fourth order in Parker’s expansion is actually compatible with the traditional Bouguer anomaly calculated with FA2BOUG, and that higher orders do not introduce significant changes. The comparison reveals that the difference between both methods in the Argentine continental margin has a quasi bimodal statistical distribution. The main disadvantage in using routines based on Parker's expansion is that an average value of the topography is needed for the calculation and, as the margin has an abrupt change of the topography in the continental slope area, it causes a bimodal distribution. It is worth noticing that, as expected, the most important differences between both methods are located over the continental slope both in complex structures such as part of the shared margin, as well as in isolated points where there are contributions from short wavelength or rugged topography.